Bayesian network-based video QoE assessment method using image sustained damage analysis - Yang GENG; Su-jie SHAO; Shao-yong GUO; Peng YU (Tongxin xuebao)
At present,the influence of the image sustained damage is often neglected in the objective method of the quality of user experience in video service.In view of this problem,the effect of the visible duration of visual impairment on the quality of the user experience was discussed.At the same time,the objective reason of continuous damage was analyzed,and a Bayesian network was constructed which included hierarchical objective index and subjective evaluation result.On this basis,a no-reference evaluation method for the quality of video service experience was proposed,and the accuracy of the method is verified by subjective test.